Fadila Annisa Ablation in Patients with Idiopathic Fascicular Left Ventricle Tachycardia at Tangerang District General Hospital ABSTRACT Ventricular tachycardia (VT) originating from Fascicular LV usually occurs in patients without structural heart dis - Fadilla Annissa (ARKAVI [Arsip Kardiovaskular Indonesia), 2019)
Ventricular tachycardia (VT) originating from Fascicular LV usually occurs in patients without structural heart disease , but it is not uncommon to produce incessant VT in the case of Tachycardiomyopathy. Catheter ablation is a very effective therapy for VT that is resistant to drug therapy or in patients who do not want to undergo daily therapy with the success of VT elimination estimated in> 90% of patients. The author uses descriptive method. The writing time was held in February 2018 with a total of 1 IFLVT patients. The results of this case study found one patient identified with IFLVT, with an ECG before ablation indicated a RBBB pattern and a left axis deviation axis indicated the classification of posterior IFLVT. and has been successfully ablated used radio frequency waves and tachycardia is noninducibility even with aggressive pacing. Purkinje Potentials and Diastolic Potentials are useful markers for successful ablation procedure because they participate in reentry circuits. Keyword: Ventricle tachycardia, IFLVT, AblationFadila Annisa Ablasi pada Pasien Idiopathic Fascicular Left Ventricle Tachycardia Ventrikel Takikardi (VT) yang berasal dari Fascicular LV biasanya terjadi pada pasien tanpa struktur jantung yang abnormal, Tetapi tidak jarang dapat menghasilkan VT yang bersifat incessant pada kasus Tachycardiomyopathy. Ablasi kateter merupakan terapi yang sangat efektif untuk VT yang resisten terhadap terapi obat atau pada pasien-pasien yang tidak mau menjalani terapi harian dengan keberhasilan eleminasi VT diperkirakan pada >90% pasien. Penelitian menggunakan metode deskriptif. Waktu penulisan dilaksanakan pada Februari 2018 dengan jumlah kasus sebanyak 1 pasien IFLVT. Hasil dari studi kasus ini didapatkan satu orang pasien yang teridentifikasi IFLVT, dengan EKG sebelum ablasi menunjukkan RBBB pattern dan sumbu deviasi aksis kiri yang menandakan klasifikasi dari IFLVT posterior, dan telah berhasil diablasi dengan menggunakan gelombang radio frekuensi kemudian takikardia tidak tercetus kembali bahkan dengan pemicuan yang agresif.. Purkinje Potentials dan Diastolic Potentials menjadi penanda yang berguna dalam prosedur ablasi yang sukses karena berpartisipasi dalam sirkuit reentry. Kata Kunci: Ventrikel takikardi, IFLVT, Ablasi